2019
DOI: 10.1007/s40615-019-00561-4
|View full text |Cite
|
Sign up to set email alerts
|

“I Try Not to Even Think About My Health Going Bad”: a Qualitative Study of Chronic Kidney Disease Knowledge and Coping Among a Group of Urban African-American Patients with CKD

Abstract: Context: African Americans with chronic kidney disease (CKD) are more likely to progress to end-stage renal disease (ESRD). However, African Americans are less likely to receive care to delay progression of their CKD and to prepare for ESRD treatment. Objective:The objectives of the study are to understand knowledge among urban, African-American patients diagnosed with CKD and to discover ways they managed their illness and prepared for kidney disease progression.Design: A qualitative study was conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…What makes it stressful is not its physical impact but its progression towards kidney failure. Previous studies showed similar results [ 31 , 32 ]. Patients' current health status may lead to cognitive avoidance, which may delay decision-making [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…What makes it stressful is not its physical impact but its progression towards kidney failure. Previous studies showed similar results [ 31 , 32 ]. Patients' current health status may lead to cognitive avoidance, which may delay decision-making [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies showed similar results [ 31 , 32 ]. Patients' current health status may lead to cognitive avoidance, which may delay decision-making [ 31 , 33 ]. It might nonetheless be adaptive in the short term, especially at stage 3, if it does not prevent patients from engaging in healthy behaviors.…”
Section: Discussionsupporting
confidence: 85%
“…They could see why I could chose it, that it did fit in with my life better and, if anything, I'd made up my mind anyway and after I was talking to them, it confirmed it.” [ 23 ] Supporting the patients’ relationships Healthcare professionals. Patients valued attentive, non-judgemental medical care but sometimes found this was lacking, creating a sense of distrust and disrespect Engaging patients in educational conversations about CKD and creating a space to listen and answer questions could improve their relationships with healthcare professionals [ 20 , 22 26 ] Moderate confidence Minor concerns regarding methodological limitations, coherence and relevance and moderate concerns regarding adequacy “And everybody always- were just were really concerned and spent time with me and explained and whatever, so it was really a partnership in making sure that I stayed healthy... I liked how they coordinated and they’d be like, ‘ok, you’re going to have to see three doctors, but let’s just poke you once.’ So then I would bring the requisition to everybody and then they would fill out one form so that I’m [not] going getting blood work every, you know, day...” [ 20 ] “He should take a little more interest, rather than just fob me off and say, go see another doctor, because it may be related or not related to the kidney problem.” [ 26 ] “I think that one of the things we all have felt that I don't think anyone has said, is the problem of people meaning to tell us or give us a misconception of how you are going to feel.” [ 25 ] Peers.…”
Section: Resultsmentioning
confidence: 99%
“…Este dato resulta reseñable porque los pacientes de otros estudios, con una enfermedad crónica no perciben su enfermedad como tan amenazante (Adrián-Arrieta & Casas-Fernández, 2017;Weldam et al, 2013). No obstante, cabe señalar que hay pacientes de nuestra muestra que no perciben la ERCA como amenazante, quizás debido a un menor conocimiento acerca de ella o a un proceso de negación de la enfermedad (Lissanu et al, 2019).…”
Section: Discussionunclassified